O Encontro Nacional de Educação Matemática-ENEM: como espaço formativo dos professores que lecionam matemática nos anos iniciais do ensino fundamental - Bezerra, Francisco Arnaldo Lopes (2020)
The National Meeting of Mathematical Education has been held since 1982 by the Brazilian Society of Mathematical Education. This event has been or where teachers publish and discuss their research on the most diverse topics in the area of Mathematics Education. In this study, the National Meeting of Mathematical Education is presented, as a training space for teachers who teach mathematics in the early years of elementary school. It does not refer to the public, the event includes teachers from the Basic Education and Higher Education network, as well as undergraduate and graduate students and researchers working in the area of scientific research in Mathematics Education. Thus, the objective is to analyze how ENEM contributions as a formative space for mathematics for teachers in the early years of elementary school. looking at the works in the oral presentation modality and, more specifically, presenting the academic productions presented in the 2016 and 2019 editions, pointing out which subsidies are highlighted in these works, especially with regard to the thematic units of mathematics present in the National Common Curricular Base - BNCC (BRASIL, 2018), especially the Geometry and Probability and Statistics units. The analyzes of the works on these themes were discussed mainly, in the light of theorists such as D’Ambrósio (1995), Santos (2018) and Becker (1993). The research is qualitative in nature, supported mainly by the methodological assumptions of Lakatos (1978) and Popper (1974). The research steps comprised: (i) collection; (ii) selection; (iii) analysis; and (iv) organizing the data in an online environment. For teachers to enjoy, the works, with pedagogical guidance, are displayed on the research group's website weaving cognitive learning networks. The results pointed to the need to create a database so that it is accessible to teachers, with analyzes of the ANAIS of the 2016 and 2019 editions, with regard to the Geometry and Probability and Statistics units. It can also be presented as a result that the analyzed works can contribute to the development of teacher education through research. This work is considered relevant, because this material organized and accessible to teachers will serve as a reference for them, as well as for the general public that works in the formation and teaching of mathematics in the early years of Elementary School.